Sex-specific differences in sleep-disordered breathing and nocturnal hypoxemia in chronic thromboembolic pulmonary hypertension and chronic thromboembolic pulmonary disease - Li, Hui-Ting; Yuan, Ping; Zhao, Qin-Hua; Gong, Su-Gang; Jiang, Rong; Li, Jin-Ling; Liu, Hong-Ting; Qiu, Hong-Ling; Wu, Wen-Hui; Luo, Ci-Jun; He, Jing; Wang, Lan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Although chronic thromboembolic pulmonary hypertension (CTEPH) and chronic thromboembolic pulmonary disease (CTEPD) are known to be accompanied by symptoms associated with sleep-disordered breathing (SDB) and nocturnal hypoxemia, the sex-specific differences of SDB and nocturnal hypoxemia in patients with CTEPH and CTEPD remain unknown. Methods: Between July 2020 and August 2022, data were retrieved from 57 males and 63 female patients with CTEPH and CTEPD who underwent sleep study at Shanghai Pulmonary Hospital. Nocturnal mean SpO2 (mean SpO2) <90% was defined as nocturnal hypoxemia. Logistic and linear regression analysis was performed to assess the predictive value of sleep study indices to hemodynamic parameters. Receiver operating characteristic (ROC) curve was applied to analyze the specific parameters to predict the risk of CTEPH. Results: SDB was similarly present in males and females, and both sexes predominantly had obstructive sleep apnea (OSA); more women were diagnosed with nocturnal hypoxemia (32% vs. 7%, p=0.002). SaO2 was negatively associated with mean pulmonary arterial pressure (mPAP) in men (p<0.001), whereas the ratio of nocturnal SpO2 <90% of the total monitoring time (T90%) was positively correlated with mPAP. Mean SpO2 was an independent predictor for pulmonary vascular resistance and cardiac output in women (p=0.001, p<0.001, p=0.001 respectively). T90%, SaO2, and minimal SpO2 were combined to develop a new composite parameter: hypoxemia scoring index (HSI). ROC curve analysis indicated that HSI levels of 0.55 could discriminate CTEPH from CTEPD with a sensitivity of 92.3% and specificity of 87.5% in female patients (an area under the curve, 0.937; 95% CI: 0.879–0.995, p<0.001). Conclusion: Sex-specific nocturnal hypoxemia was present in patients with CTEPH or CTEPD. In female patients, the HSI showed high capacity for predicting the risk of CTEPH.